Combined subcritical thresholds of glenoid and humeral sided bone loss are predictive of failure after arthroscopic Bankart repair. Issue 7 (31st July 2020) - Kane, Gillian; Golan, Elan; Wilson, Kevin; Lesniak, Bryson; Lin, Ryan Li Albert
Objectives: Glenoid and humeral sided bone loss are both independent risk factors for failure after arthroscopic Bankart repair. The purpose of this study was to determine the combined effect of subcritical levels of humeral and glenoid sided bone loss on failure after arthroscopic Bankart repair. Methods: 171 individuals with minimum 2 years follow up who underwent primary arthroscopic Bankart repair between 2007-2015 were included in this study. Glenoid and humeral sided bone loss were measured using the glenoid track model. Cases were defined as individuals who sustained a subluxation or dislocation event after the index procedure, while controls were defined as individuals who did not. Subjects were stratified by age (20+ versus < 20 years). Receiver operating curves (ROC) were generated to determine the threshold of glenoid and humeral sided bone loss that could best predict failure. Results: There were 53 cases and 118 controls. Increased glenoid (p < .001) and humeral-sided (p = .013) bone loss independently predicted failure. ROC analysis demonstrated that threshold values of 12% glenoid (AUC = 0.62) and 13 mm humeral (AUC = 0.60) bone loss were predictive of failure. Combined subcritical thresholds of 10% glenoid and 10 mm humeral sided bone loss successfully predicted outcomes of 49/56 (87.5%) individuals over age 20 and 79/117 (67.5%) individuals under age 20. Humeral and glenoid sided bone loss had an additive effect on risk of failure in older individuals while glenoid sided bone loss was primarily responsible for failure in younger individuals. Conclusion: Both glenoid and humeral sided bone loss are predictive of failure after arthroscopic Bankart repair. Combined subcritical thresholds of glenoid and humeral sided bone loss accurately predict failure, particularly in individuals over the age of 20. These results suggest that individuals with subcritical bipolar lesions may be at higher risk of failure after arthroscopic Bankart repair than previously thought. Table 1. % Failure P value ≥Age 20 years Glenoid bone loss > 10%, Hill-Sachs > 10 mm 87.5% (7/8) P < .001 Glenoid bone loss > 10%, Hill-Sachs < 10 mm 33.3% (2.6) P = .53 Glenoid bone loss < 10%, Hill-Sachs > 10 mm 30% (3/10) P = .58 Glenoid bone loss < 10%, Hill-Sachs < 10 mm 3.1% (1/32) P < .001 Age < 20 years Glenoid bone loss > 10%, Hill-Sachs > 10 mm 62.5% (5/8) P = .080 Glenoid bone loss > 10%, Hill-Sachs < 10 mm 70.6% (12/17) P = .001 Glenoid bone loss < 10%, Hill-Sachs > 10 mm 23.6% (4/17) P = .32 Glenoid bone loss < 10%, Hill-Sachs < 10 mm 25.3% (19/75) P = .007